The crucial role of H-bonding in the mechanisms of reactions with diamines in aprotic solvents - Alvaro, Cecilia Elisabeth Silvana (2011)
In the widely reported mechanistic studies of Aromatic Nucleophilic Substitutions (ANS) most of the discussions are centered in the nature of the halo-nitro-aromatic substrates, the basicity of the nucleophile and the polarity or dipolarity of the solvent. However, in the reactions of monofunctionalized amines with aromatic substrates bearing poor nucleofuges carried out in solvents of low permittivity, weak non-covalent interactions, such as intra- and/or inter-molecular H-bonding, play a significant role. When these special features concur in the reaction system, a mechanism, called the “dimer nucleophile mechanism”, operates in which a third-order in amine kinetic law is obeyed. The mechanism has been properly characterized by abundant evidence, showing the influence of weak non-covalent interactions, due to the nucleophile nature, the substrates used and the reaction medium. In the present paper, we discuss new examples of that mechanism to show the crucial role of H-bonding. Several aspects were studied: the influence of the nucleophile structure (specially its capacity of developing intra- and/or intermolecular hydrogen bond interactions); the “resonance-assisted” H-bond; and the effect of aprotic hydrogen bond acceptor (HBA) co-solvent/additives. A comprehensive further treatment of kinetic results is described including reactions where the first-step or the second-step are rate determining.